ANALISIS TERHADAP DAKWAAN JAKSA PENUNTUT UMUM TERHADAP TINDAK PIDANA PEMALSUAN AKTA JUAL BELI DALAM PUTUSAN PENGADILAN NEGERI CIBINONG NOMOR 282/PID.B/2020/PN.CBI. - Calvin Rafly Hadi Pradana; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2022)
The first trial in the criminal procedural law begins with an investigation, then an investigation, aprosecution, and a judge's decision. With regard to the criminal process of forgery of documents, theDistrict Attorney's Of ice prepares a letter of indictment that corresponds to the elements of the crimecommitted by the defendant and meets the requirements of the indictment letter, that is, formal andmaterial requirements. The indictment is the basis of the inquest in court, on the basis of indictment aperson is heard and prosecuted before the trial. The public prosecutor should be careful when applyingthe relevant. articles in the case so that injustice is not committed. How is the analysis towardsindictment prosecutor, public prosecutor, against, Follow, punishment, forgery, deed of sale andpurchase in the Judgment Court Cibinong Country Number 282/Pid.b/2020/PN. Cbi. regarding theindictment of the Public Prosecutor Research legal materials. In, the type is normative with theapproach. legislation. and approach case. Based on the results of the deep analysis. the writing of thisthesis has been shown to be inaccuracy in the formulation of the letter, the prosecution's indictment,the Public. Public Prosecutor on a. not. careful. does not include article. 264 verses. (1) 1st. CriminalCode. in the formulation of the indictment. Related. Criminal. forgery. letter. whose object is anauthentic deed then the Defendant should have been charged based on. Article 264. verse. (1). 1stCriminal Code.